Development of Learning Strategies Textbook Based on Multiple Intelligences: Theoretical and Practical Overview in SD/MI / Pengembangan Buku Teks Strategi Pembelajaran Berbasis Multiple Intelligences: Tinjauan Teoritis dan Praktis di SD/MI - Muhamad Afandi (STAI Ma'had Aly Al-Hikam Malang, 2021)
This development research aims to: (1) Describe the validity of multiple intelligencesbased learning strategy textbook development: theoretical and practical reviews in SD/MI (2) Describe the practicality of developing multiple intelligences-based learning strategies textbooks: theoretical and practical reviews in SD/MI , and (3) to describe the effectiveness of the development of multiple intelligences-based learning strategy textbooks: theoretical and practical reviews in SD/MI. This development research uses the four-D (4-D) models, namely: define, design, develop and disseminate. The data collection method uses a questionnaire (for validation of material experts, media experts, and linguists), tests for the assessment of learning outcomes, and documentation to collect research supporting data. The data analysis technique uses percentage calculations to determine the level of validity, practicality, and effectiveness of the product being developed. The results of this study include: (1) Development of multiple intelligences-based learning strategy textbooks: theoretical and practical reviews in SD/MI in valid categories from the aspects of material, media, and language.(2) Development of multiple intelligences-based learning strategy textbooks: theoretical and practical reviews in SD/MI which are practically applied in learning. (3) Development of multiple intelligences based learning strategy textbooks: theoretical and practical reviews in SD/MI are effective in achieving learning outcomes.